Development of competitiveness of the industry of cattle stockbreeding in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
In the given article the problems of cattle stockbreeding in the Republic of Kazakhstan are considered. Along with it the detailed analysis of the contemporary condition of cattle stockbreeding is conducted for the period from 2007 to 2012 by the rates of: dynamics of cattle number, quantity by economies categories, productivity of livestock, meat production and meat consumption per capita. The author revealed the basic reasons of lag of the stockbreeding branch from world meat exporters (small-scale production, low race of cattle, insufficient stern maintenance and weak vet service) on the basis of statistical data. In the article the weak and strong sides of Kazakhstan branch of stockbreeding are analyzed before entry of the country into WTO and the ways of improving the competitiveness of beef cattle according to national peculiarities are offered. The first results of introduction of “Development of the export potential of meat” Project are considered in the Republic of Kazakhstan. The issues of state support and prospects of cattle breeding development in Kazakhstan are considered.
Keywords: Competitiveness of livestock; small-scale production; meat export; preferential crediting of agriculture subjects